Probiotic Supplementation During Human Pregnancy Affects the Gut Microbiota and Immune Status - Chen, Yuyi; Li, Zhe; Tye, Kian Deng; Luo, Huijuan; Tang, Xiaomei; Liao, Yu; Wang, Dongju; Zhou, Juan; Yang, Ping; Li, Yimi; Su, Yingbing; Xiao, Xiaomin (Frontiers in Cellular and Infection Microbiology, 2019)
The consumption of probiotics and fermented foods has been very popular in recent decades. The primary aim of our study was to evaluate the effect of probiotics on the gut microbiota and the changes in inflammatory cytokines after an average of 6.7 weeks of probiotic administration among normal pregnant women. Thirty-two healthy pregnant women at 32 weeks of gestation were recruited and divided into two groups. The probiotic group ingested combined probiotics until after birth. The base characteristics of the probiotics and control groups showed no significant differences. The structure of the fecal microbiota at the genus level varied during the third trimester, and administration of probiotics had no influence on the composition of the fecal microbiota however, many highly abundant taxa and core microbiota at the genus level changed in the probiotic group when compared to the control group. The analysis of cytokines showed that IL-5, IL-6, TNF-α, and GM-CSF had equal levels between the baseline and control groups but were significantly increased after probiotic administration (baseline = control < probiotics). Additionally, levels of IL-1β, IL-2, IL-12, and IFN-γ significantly increased among the three groups (baseline < control < probiotics). This result demonstrated that probiotics helped to shift the anti-inflammatory state to a pro-inflammatory state. The correlation analysis outcome suggested that the relationship between the microbiota and the cytokines was not strain-dependent. The gut microbiota varied during the third trimester. The probiotics demonstrated immunomodulation effects that helped to switch over to a pro-inflammatory immune state in the third trimester, which was important for labor.